Answer: x = 1
==============================================
There are two ways to solve
First method is dividing both sides by -7, then subtract 7 from both sides like so
-7(x+7) = -56
x+7 = -56/(-7)
x+7 = 8
x = 8-7
x = 1
Or
We could distribute first, add 49 to both sides, then divide both sides by -7
-7(x+7) = -56
-7x-49 = -56
-7x = -56+49
-7x = -7
x = -7/(-7)
x = 1
Either way we get the same result.
--------------------
Checking the answer:
Plug x = 1 into the original equation. Simplify.
-7(x+7) = -56
-7(1+7) = -56
-7(8) = -56
-56 = -56
The answer is confirmed since we got the same number on both sides.